Superior cardiac mechanics without structural adaptations in pre-adolescent soccer players. (1st September 2020) - Beaumont, Alexander; Oxborough, David; George, Keith; Rowland, Thomas W; Sculthorpe, Nicholas; Lord, Rachel; Unnithan, Viswanath B
Abstract : Aims: This study aimed to evaluate left ventricular structure, function and mechanics, in highly-trained, pre-adolescent soccer players compared with age- and sex-matched controls. Design: The study design was a prospective, cross-sectional comparison of left ventricular structure, function and mechanics. Methods: Twenty-two male soccer players from two professional youth soccer academies (age: 12.0 ± 0.3 years) and 22 recreationally active controls (age: 11.7 ± 0.3 years) were recruited. Two-dimensional conventional and speckle tracking echocardiography were used to quantify left ventricular structure, function and peak/temporal values for left ventricular strain and twist, respectively. Results: End-diastolic volume index was larger in soccer players (51 ± 8 mm/(m 2 ) 1.5   vs . 45 ± 6 mm/(m 2 ) 1.5 ; p  = 0.007) and concentricity was lower in soccer players (4.3 ± 0.7 g/(mL) 0.667   vs . 4.9 ± 1.0 g/(mL) 0.667 ; p  = 0.017), without differences in mean wall thickness between groups (6.0 ± 0.4 mm vs . 6.1 ± 0.5 mm; p  = 0.754). Peak circumferential strain at the base (–22.2% ± 2.5% vs . –20.5% ± 2.5%; p  = 0.029) and papillary muscle levels (–20.1% ± 1.5% vs . –18.3% ± 2.5%; p  = 0.007) were greater in soccer players. Peak left ventricular twist was larger in soccer players (16.92° ± 7.55° vs . 12.34° ± 4.99°; p  = 0.035) and longitudinal early diastolic strain rate was greater in soccer players (2.22 ± 0.40 s –1   vs . 2.02 ± 0.46 s –1 ; p  = 0.025). Conclusions: Highly-trained soccer players demonstrated augmented cardiac mechanics with greater circumferential strains, twist and faster diastolic lengthening in the absence of differences in wall thickness between soccer players and controls.